Using of chicken and turkey meat in salami production - Mustafa Atasever; Abdullah Keleş; Ahmet Güner; K.Kaan Tekinşen (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine salami production Irom turkey and chicken meats. These poultry meals were mixed in different ratios in production and physical, chemical, microbiological and sensory properties of the products were examined. Samples were different in emulsion stability, moisture, pH value and fat contents. There were no differences in microbiological analyses. In sensory evaluations, samples produced from turkey meal were obtained low scores than other groups. Chicken salami was more preferred amoung the groups. It is concluded that turkey meat could be combined with chicken meat in salami production in a portion of 50 %.